Examining the Reproductive Rights in the Wake of COVID-19 Pandemic in Nigeria - Nnawulezi Uche; Bosede Remilekun Adeuti (Indonesian Journal of Law and Society, 2021)
The prospect of achieving sustainable reproductive rights protection in the wake of the COVID-19 pandemic in Nigeria has remained an intractable problem. To identify and recognize reproductive rights, it is necessary to comprehend that reproductive right embraces certain human rights recognized in national and international laws, including international human rights’ documents. This paper examined the existing Nigeria laws on reproductive and health rights and ascertained the extent to which it had continually and predictably addressed the reproductive rights protection problem. There was a significant protection gap in the national human rights architecture. At the international level, among the poorer adolescent girls between the age of 15-19 years, it frequently resulted in early pregnancy and, of course, unsafe abortion. Thus, this gap related in particular to questions on lack of access to family planning services. This paper argued that improvement of reproductive and sexual health went far beyond the right to life and the right to health of women and girls. To guarantee Nigeria's reproductive rights, a more integral response to these critical human rights and development challenges could address Nigeria's protection gap. This paper adopted an analytical and qualitative approach by referring to existing pieces of literature achieved by the synthesis of ideas. This paper concluded that the adoption of a new approach to policies and programs on preventable maternal mortality and morbidity guaranteed the right to attain the highest standard of sexual reproductive health in Nigeria. KEYWORDS: Reproductive Rights, Health Issues, COVID-19 Pandemic, Nigeria.